2021
DOI: 10.1001/jamaoncol.2021.1932
|View full text |Cite|
|
Sign up to set email alerts
|

Neoadjuvant Trastuzumab, Pertuzumab, and Docetaxel vs Trastuzumab Emtansine in Patients With ERBB2-Positive Breast Cancer

Abstract: IMPORTANCE Trastuzumab emtansine (T-DM1) is presently approved for treatment of advanced breast cancer and after incomplete response to neoadjuvant therapy, but the potential of T-DM1 as monotherapy is so far unknown.OBJECTIVE To assess pathologic complete response (pCR) to standard neoadjuvant therapy of combination docetaxel, trastuzumab, and pertuzumab (DTP) vs T-DM1 monotherapy in patients with ERBB2 (formerly HER2)-positive breast cancer. DESIGN, SETTING, AND PARTICIPANTSThis randomized phase 2 trial, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Of the 3010 studies identified, 32 published studies [5,[10][11][12], including 21 RCTs [10,11,29,31,32,34,35,[38][39][40][43][44][45][46][47][48][49][50][51]53,54], were eligible for inclusion within this analysis (Figure 1). Among these, four anti-HER2 medicines (i.e., T, L, P, T-DM1) were evaluated in 11 regimens (i.e., TC, LC, PC, PT, T-DM1P, PTC, LTC, T-DM1LC, T-DM1PC, PTC_T-DM1P, T-DM1) along with chemotherapy alone (see Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 3010 studies identified, 32 published studies [5,[10][11][12], including 21 RCTs [10,11,29,31,32,34,35,[38][39][40][43][44][45][46][47][48][49][50][51]53,54], were eligible for inclusion within this analysis (Figure 1). Among these, four anti-HER2 medicines (i.e., T, L, P, T-DM1) were evaluated in 11 regimens (i.e., TC, LC, PC, PT, T-DM1P, PTC, LTC, T-DM1LC, T-DM1PC, PTC_T-DM1P, T-DM1) along with chemotherapy alone (see Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The individual study characteristics are presented in Table 1. Twelve RCTs were comprised of two arms, for which TC vs. C was the most common treatment comparison (5 RCTs) [30,32,34,35,45], followed by TC vs. LC (2 RCTs) [12,46], with the remainder comprising unique comparisons [10,[49][50][51]54]. Eight RCTs included three arms with seven RCTs comparing TC vs. LC vs. LTC [31,40,43,44,47,48,53]; a single RCT compared PTC vs. T-DM1PC vs. PTC_T-DM1P [11], while one trial comprised four arms that compared TC vs. PC vs. PT vs. PTC [38].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For systemic therapy, this has been addressed in patients with HER2-positive disease. The PREDIX HER2-trial compared docetaxel, trastuzumab and pertuzumab to T-DM1 and found similar rates of pathologic complete response and event-free survival in both arms [ 20 , 21 ]. Results on survival outcomes are pending.…”
Section: De-escalation Approachesmentioning
confidence: 99%